PERAN DPR RI TERHADAP ISU PERUBAHAN IKLIM DI INDONESIA MELALUI FORUM INTERPARLEMEN 2019-2022 - Anna Pratiwi; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research analyzes the role of the Indonesian House of Representatives (DPR RI) in addressing the issue of climate change. Climate change is a pressing global topic that affects the environment, including Indonesia. It is considered the 6th National Priority in the National Medium-Term Development Plan (RPJMN) for the period 2019-2024. Addressing climate change requires the involvement of various stakeholders, including the parliament. The DPR RI has three main functions and an additional function, which is representation. One form of representation is through parliamentary diplomacy, which supports the diplomatic efforts of the government. This study employs a qualitative method, using data collection techniques such as literature review from books, journals, articles, websites, and interviews with experts from the Inter-Parliamentary Cooperation Agency (BKSAP) to strengthen the understanding of the role of the DPR RI. The research applies the perspectives of Constructivism and Parliament Theory to evaluate the role and identify the root causes of the issues in this study. The findings of this research demonstrate that the DPR RI has been actively addressing climate change through parliamentary diplomacy from 2019 to 2022. The DPR RI participated in 22 international forums, produced 16 cooperation agreements, and provided representation and legitimacy in understanding climate change legislation. The role of the DPR RI during the period of 2019-2024 indicates that it fulfills both functions by actively engaging in forums and knowledge exchange as the basis for legislation. Keywords: Role, Climate Change, DPR RI, Interparliament, Forums, BKSAP